Evaluation of Achievement Development Program of Bengkulu Tennis School - Dedi Ansyah; Damrah; Alnedral; Asep Sujana Wahyuri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The problem in this study is the factors that influence tennis coaching including organizational management factors, athlete training, competition programs and training programs for related parties involved in solving the problem. This study aims to evaluate the implementation of the Bengkulu Tennis School Athlete Achievement Development Program using the CIPP evaluation model (Context, Input, Process, Product). The evaluation model used in this study is the CIPP model. The research subjects consisted of administrators, coaches, and athletes. Data collection techniques using the method of observation, interviews, documentation, and questionnaires. The data analysis technique in this research is descriptive quantitative and qualitative analysis. The results of this study are (1) Context Evaluation, getting a good rating, (2) Input Evaluation, get a good rating, (3) Process Evaluation gets a good rating, (4) Product Evaluation gets a good rating. In this case it is classified as a good criterion in the standard of success of a development. The conclusion from the research results of the Evaluation of the Bengkulu Tennis School Athlete Achievement Development Program is in the category both as a whole and in the aspects of Context, Input, Process, and Product.